A Legal Reconstruction of Criminal Liability for the Dissemination of False News (Hoaxes) Based on the New Criminal Code and Updates to the ITE Regulations - Muliyani; Maria Ferba Edytia Simanjuntak; Rayani Saragih (Indonesian Journal of Advanced Research, 2026)
The escalation of the spread of false information (hoaxes) in the virtual space has shifted from a digital ethics issue to a real threat to public order and security. This normative research aims to examine the Indonesian criminal law architecture in ensnaring the spread of fake news perpetrators following the enactment of the new regulatory package, while simultaneously identifying the dynamics of penal and non-penal countermeasures. The research method applied is normative juridical through a regulatory-legal approach (statutory approach) and a contextual approach (conceptual approach). Primary legal materials include Law Number 1 of 2024 concerning the Second Amendment to the ITE Law and the Criminal Code (KUHP), Law Number 1 of 2023. The research results confirm that the qualifications for the act of spreading fake news have undergone a rigid reconceptualization. Specifically (lex specialis), Article 28 paragraph (3) in conjunction with Article 45A of Law Number 1 of 2024 criminalizes macro-hoaxes that trigger public concern, while in general (lex generalis), Article 263 and Article 264 of the New Criminal Code integrate elements of intentional and negligent offenses in reporting uncertain news. The main obstacles to law enforcement are the elimination of regulatory fragmentation, disparities in technological competence of officials, limited digital forensic infrastructure, and a deficit in critical literacy among the community. Research recommendations encourage the unification of interpretations of potential offense elements and optimization of content moderation functions by the government to maintain a balance between freedom of expression and public protection.